Basin Focal Project Niger - Charles Clanet, J.; Ogilvie, A. (CGIAR Challenge Program on Water and Food, 2009)
Challenge Program Water and Food: Basin Focal Project NIGER Faced with increasing food and water insecurity as a result of climatic and anthropogenic (demography, land use) changes, the CGIAR Challenge Program for Water and Food commissioned research in 10 river basins to study the links between water, food and poverty. Looking at the Niger river basin, we carry out a diagnosis of the hydrologic and agronomic potential, before attempting to identify how good agricultural water management may reduce vulnerability in the region, and preserve local ecosystems. Major future threats and opportunities, as well as the influence of institutions on water and agricultural development are discussed. The study indicated that while many technical solutions are available and identified, institutional issues as well as generalized poverty undermine their sustained uptake by communities. Further research is required in order to determine how to overcome socio-economic and institutional issues.